2014
DOI: 10.1007/s11099-014-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

Maize growth and developmental responses to temperature and ultraviolet-B radiation interaction

Abstract: Plant response to the combination of two or more abiotic stresses is different than its response to the same stresses singly. The response of maize (Zea mays L.) photosynthesis, growth, and development processes were examined under sunlit plant growth chambers at three levels of each day/night temperatures (24/16°C, 30/22°C, and 36/28°C) and UV-B radiation levels (0, 5, and 10 kJ m -2 d -1 ) and their interaction from 4 d after emergence to 43 d. An increase in plant height, leaf area, node number, and dry mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…For a number of studies, organisms were grown at the ambient temperature over several months or years, during which time the temperature fluctuated and the treatment represented an increase by a given number of degrees C above the ambient temperature (Supporting Information Table S1). For instance, in the study of Singh, Reddy, Reddy, and Gao (), the temperature level 24/16 °C (day/night) was taken as the control, and the temperature levels 30/22 °C and 36/28 °C were considered individually as treatments (Supporting Information Table S1). Ideally, the optimum temperature should be considered as the control.…”
Section: Methodsmentioning
confidence: 99%
“…For a number of studies, organisms were grown at the ambient temperature over several months or years, during which time the temperature fluctuated and the treatment represented an increase by a given number of degrees C above the ambient temperature (Supporting Information Table S1). For instance, in the study of Singh, Reddy, Reddy, and Gao (), the temperature level 24/16 °C (day/night) was taken as the control, and the temperature levels 30/22 °C and 36/28 °C were considered individually as treatments (Supporting Information Table S1). Ideally, the optimum temperature should be considered as the control.…”
Section: Methodsmentioning
confidence: 99%
“…showed reduction in plant height (by 7%), leaf area (by 15%), and photosynthetic rate (by 26%) with the same UV-B treatments (Koti et al 2007). Additionally, UV-B increased chemical composition of UV-absorbing compounds and pigments in maize leaves by 51% at 10 kJ m -2 d -1 UV-B (24/16°C) (Singh et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Approximately 20% of crops are sensitive to UV-B radiation regarding dry mass reduction (Teramura 1983). Previous studies had already covered soybean (Koti et al 2007), cotton (Kakani et al 2003), and maize (Singh et al 2014, Wijewardana et al 2016. For example, it was found that 10 kJ m -2 d -1 UV-B (the projected UV-B level) had multiple negative effects on maize (Zea mays L.) including reduced plant height (by 36%), leaf area (by 22%), and photosynthetic rate (by 5-15%) compared to 0 kJ m -2 d -1 treatment (Singh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cereal Research Communications 45, 2017 The effect of drought stress and UV-B radiation on crop plants varies depending on the intensity of stress and the crop growth stage (Singh et al 2014). The effect of UV-B on plants depends on radiation rates and wavelength, and has a cumulative character; the longer the time of exposure, the greater the effect of its action (Bandurska et al 2013).…”
mentioning
confidence: 99%
“…Some of the deleterious effects of UV-B radiation on plants include DNA damage, dilation and disintegration of cellular membranes, photooxidation of leaf pigments and phytohormones, and inhibition of photosynthesis (Reddy et al 2013). The UV-B protective mechanism in plants involves photoreactivation to repair DNA damage, accumulation of UV-B absorbing compounds (e.g., phenolic compounds) and waxes in the leaf epidermis to partially block UV-B radiation (Singh et al 2014). Therefore, the plant responses are not stress responses but are rather associated with UV-B protection or amelioration of damage (Bandurska et al 2013).…”
mentioning
confidence: 99%